Physical Properties of Nanostructured CdO Films from Alkaline Baths Containing Saccharin as Additive - Bünyamin Şahin (The Scientific World Journal)
Nanostructured cadmium oxide (CdO) films were fabricated on glass substrates from alkaline baths containing saccharin as an additive by a successive ionic layer adsorption and reaction (SILAR) method. The effects of saccharin concentration in the bath on the structural, morphological, and optical properties were studied by means of scanning electron microscopy (SEM), X-ray diffraction (XRD), photoluminescence, and Raman spectroscopy. The analyses showed that the surface morphologies, XRD peak intensities, Raman spectroscopy, and photoluminescence properties of CdO films changed with saccharin concentration. From the results, it can be said that morphological characteristic and optical properties of the films could be calibrated by adding various saccharin percentages in the growth bath.